ADOK DALAM STATUS SOSIAL MASYARAKAT LAMPUNG PEPADUN DI DESA SUKARAJA NUBAN - Maya Sari; Karsiwan karsiwan (Program Studi Pendidikan Soiologi Antropologi, FKIP-UNS, 2024)
Begawi is a traditional ceremony for taking the highest title in the Lampung Pepadun tradition which has been carried out from time to time by the community to include cultural values. The aim of this research is to find out how to get adok in the traditional Lampung pepadun begawi in Sukaraja Nuban Village, Batanghari Nuban District, East Lampung Regency which is in the highland and inland areas of Lampung including the Abung, Way Kanan, Way Seputih (Pubian) areas. is ulun (person). Lampung Sukaraja Nuban people still adhere to their local wisdom, one of which is the ritual of giving traditional titles during or after marriage. This article aims to explain the process of giving traditional titles to the Lampung Saibatin people and find out how giving traditional titles affects the social status of the Lampung Saibatin people. With qualitative research methods, this research uses symbolic interactionism theory as an analytical study. The results of the research explain that the procession of awarding degrees goes through several processes, including paying traditional money such as lighting fees, kissing fees, and kibau. The meaning of giving traditional titles includes respect and social status in traditional ceremonies, regulation of relationships in kinship, symbols of maturity, as well as mechanisms for preserving culture carried out from generation to generation. The implications of traditional titles for social status include roles, social recognition in the community, and as social control.Keywords: adok, begawi, dan social status AbstractBegawi merupakan sebuah upacara adat dalam pengambilan gelar tertinggi di adat lampung pepadun yang telah dilaksanakan dari zaman ke zaman oleh masyarakat dalam mencantumkan nilai-nilai kebudayaan. Tujuan penelitian ini adalah untuk mengetahui bagaimana cara mendapatkan adok dalam begawi adat lampung pepadun di Desa sukaraja nuban, Kecamatan Batanghari Nuban, Kabupaten Lampung Timur yang berada di daerah dataran tinggi dan pedalaman Lampung meliputi daerah Abung, Way Kanan, Way Seputih (Pubian) Mayoritas masyarakatnya adalah ulun (orang). Lampung Masyarakat Sukaraja Nuban masih berpegang teguh pada kearifan lokalnya, salah satunya adalah ritual pemberian gelar adat saat atau setelah perkawinan.Tulisan ini bertujuan untuk menjelaskan proses pemberian gelar adat pada masyarakat Lampung Saibatin dan mengetahui pemberian gelar adat terhadap status sosial masyarakat Lampung Saibatin. Dengan metode penelitian kualitatif, penelitian ini menggunakan teori interaksionisme simbolik sebagai kajian analisis. Hasil penelitian menjelaskan bahwa prosesi pemberian gelar melalui beberapa proses diantaranya membayar uang adat seperti dau penerangan, dau pengecupan, serta kibau. Makna dari pemberian gelar adat meliputi, penghormatan dan status sosial dalam upacara adat, pengaturan relasi dalam kekerabatan, simbol kedewasaan, serta mekanisme pelestarian budaya yang dilakukan secara turun temurun. Implikasi gelar adat terhadap status sosial meliputi, peran, pengakuan sosial dalam komunitas, dan sebagai kontrol social.Kata Kunci: adok, begawi, dan status sosial